Penal Mediation in the Criminal Law as a Shift in Social Contract Theory - I Nyoman Sukandia; I Nyoman Putu Budiartha; Ketut Adi Wirawan (Yuridika, 2020)
Social contract theory is the theory that illustrates the origin of a state formation. The theory of social contracts is composed of several instruments, including natural human rights, morals and mutual agreement (common will). Humans (individuals) surrender their rights to the ruler (state). The rights that are handed over to the state include rights in the field of public law (public interest). One of the rights in the field of public law is the right to establish norms in criminal law (ius poenale) and the right to convict (ius puniendi). Through the existence of penal mediation in Indonesia, the state's right to convict offenders is reduced. It also means that the rights handed over by individuals to the authorities (state) in social contracts are reduced. Its theoretical implication is that the right of the state to impose criminal sanctions on offenders who are based on the surrender of individual rights to social contracts, begins to be purified again with the settlement between individuals through penal mediation on violations of public (criminal) law that take place.